Game protection in the Orange Free State 1848-1910 (Historia, 2021)
The history of wildlife protection in Southern Africa has been neglected by professional historians, leaving the task almost entirely in the hands of journalists and natural scientists, untrained in the procedures of historical research. Until recently the radical revisionists focussed the attention largely on urban transformation. It was only during the late 1980's that the crucial links between town and countryside began to be explored and wildlife, next to land and labour, came into the picture.
Keywords: wildlife protection in Southern Africa; journalists; natural scientists; historical research; urban transformation; wildlife; land and labour